A Wake-Up-Call Theory of Contagion - Toni Ahnert; Christoph Bertsch (Bank of Canada, 2015)
We propose a novel theory of financial contagion. We study global coordination games of regime change in two regions with an initially uncertain correlation of regional fundamentals. A crisis in region 1 is a wake-up call to investors in region 2 that induces a reassessment of local fundamentals. Contagion after a wake-up call can occur even if investors learn that fundamentals are uncorrelated and common lender effects or balancesheet linkages are absent. Applicable to currency attacks, bank runs and debt crises, our theory of contagion is supported by existing evidence and generates a new testable implication for empirical work.
Keywords: D82; F3; G01; 330; Exchange rates; Financial stability; International financial markets